Pengaruh Media Sosial terhadap Politik di Desa Holbung, Kecamatan Sitiotio, Kabupaten Samosir - Agnes Chintya Siringoringo; Julia Ivanna (Journal on Education, 2024)
This research discusses the influence of social media on politics in Holbung Village, Sitiotio District, Samosir Regency. With the emergence and development of information technology, people's behavior has experienced a significant transformation in human thought patterns, feelings and actions. Social media is a potential tool for governments to shape public opinion and influence political participation. In the context of a democratic country like Indonesia, public opinion has a crucial role because it is the basis for government function. This study uses a library study method by collecting data through internet searching and documentation studies. Data analysis techniques include data reduction and data display. The research results show that social media plays a vital role in political participation and the formation of public opinion in the digital era, with both good and bad impacts. Nevertheless, the government needs to monitor political activities in the modern social media era. Social media is not only a communication platform, but also a place for information seeking, discussion and networking. This research aims to analyze how social media shapes political knowledge in society using a qualitative descriptive approach. The research results show that social media has a significant influence in engaging, connecting, and mobilizing political participation, although the receipt of political information via social media may vary between individuals.